Ts1 from the Brazilian scorpion Tityus serrulatus: A half-century of studies on a multifunctional beta like-toxin. (15th September 2018) - Martin-Eauclaire, Marie-France; Bougis, Pierre E.; de Lima, Maria Elena
Abstract: The Tityus serrulatus scorpion species represents a serious human health threat to in Brazil because it is among the animals that produces the most dangerous venoms for mammals in South America. Its venom has provided several highly selective ligands that specifically interact with sodium and potassium channels. During the past decades, several international groups published an increasing amount of data on the isolation and the chemical, pharmacological and immunological characterisation of its main β-toxin, Ts1. In this review, we compiled the best available past and recent knowledge on Ts1. Aside from its intricate purification, the state-of-the-art understanding concerning its pharmacological activities is presented. Its solved three-dimensional structure is shown, as well as the possible surface areas of contact between Ts1 and its diverse voltage-gated Na + channel targets. Organisations of the gene and the precursor encoding Ts1 are also tackled based on available cDNA clones or on information obtained from polymerase chain reactions of stretches of scorpion DNA. At last, the immunological studies complete with Ts1 to set up an efficient immunotherapy against the Tityus serrulatus venom are summarized. Graphical abstract: Image 1 Highlights: An updated review on the current knowledge about the Tityus serrulatus toxin Ts1. Comparison between the diverse purification procedures of Ts1. Ts1 cDNA cloning and genomic organisations. Ts1 3D-structure and structure-function relationships with its targets. Special emphasis given to Ts1 pharmacology on voltage-gated Na + channels.